LITERACY OF THE APPLICATION OF THE TRIKON STRATEGY (CONTINUOUS, CONVERGENT AND CONCENTRIC) IN THE INNOVATION OF CHOCOLATE PRODUCT VARIANTS OF FARMER GROUPS IN GUNUNGKIDUL - Fadhilah, Muinah; Hadi, Syamsul; Susanti, Dyah Ari; Rokhman, Nur; Permata, Aurel Priastyca; Rohmah, Miftakhur; Nurgiyantoro, Edi; Qayyum, Abdul (EMPOWERING HUMANITY, 2023)
Situation analysis The chocolate farmer group is located in Nglegi Hamlet RT 09 RW 03 Nglegi Patuk, Gunungkidul Regency, Yogyakarta Special Region 55561. This group has natural potential and chocolate agricultural products are quite good in Gunungkidul. The products of this chocolate farmer group are processed from the basic ingredients of chocolate, because one village is almost 50% planted with chocolate trees which are the specialty of this village. The processed products produced include coffee powder, chocolate rengginang, and chocolate bananas. The main obstacle felt by the chocolate farmer group is how to make new products that are competitive and weak graphic design so that product visualization becomes an obstacle in imagining the shape of new products and the right packaging. Solutions are needed literacy in the application of the TRIKON strategy so that formalization, intervention, and value integration in product and business development continue to run continuously because this is the hope of all members of the Chocolate Farmers Group. This service program runs according to plan and has a significant impact on understanding the literacy of packaging innovation based on 3 N (niteni, nirokke, nambahi) and visualizing the type of packaging that has local wisdom value. In addition, the main obstacle of how to determine new competitive products can be overcome by understanding the TRIKON strategy well. Literacy The application of the TRIKON Strategy (continuous, convergent and concentric) in the innovation of Farmers Group chocolate product variants is expected to be able to be applied in the face of a constantly evolving environment of volatility, uncertainty, complexity, and ambiguity.